2012
DOI: 10.1371/journal.pone.0040056
|View full text |Cite
|
Sign up to set email alerts
|

BVT.2733, a Selective 11β-Hydroxysteroid Dehydrogenase Type 1 Inhibitor, Attenuates Obesity and Inflammation in Diet-Induced Obese Mice

Abstract: BackgroundInhibition of 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) is being pursued as a new therapeutic approach for the treatment of obesity and metabolic syndrome. Therefore, there is an urgent need to determine the effect of 11β-HSD1 inhibitor, which suppresses glucocorticoid action, on adipose tissue inflammation. The purpose of the present study was to examine the effect of BVT.2733, a selective 11β-HSD1 inhibitor, on expression of pro-inflammatory mediators and macrophage infiltration in adipose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 42 publications
3
21
0
Order By: Relevance
“…Consistent with these findings, gene expression of MR was upregulated in WAT of obese mice (56). It has been reported that 11␤-HSD1 inhibition decreased WAT mass, adipocyte hypertrophy, and adipose tissue fibrosis (113), whereas it increased the expression of BAT-specific genes (including UCP1) in obese rats (73).…”
Section: Adipose Tissue Local Factors: Potential Implications Of the supporting
confidence: 82%
“…Consistent with these findings, gene expression of MR was upregulated in WAT of obese mice (56). It has been reported that 11␤-HSD1 inhibition decreased WAT mass, adipocyte hypertrophy, and adipose tissue fibrosis (113), whereas it increased the expression of BAT-specific genes (including UCP1) in obese rats (73).…”
Section: Adipose Tissue Local Factors: Potential Implications Of the supporting
confidence: 82%
“…In the present study, BVT-2733 was used as a novel selective inhibitor of 11β-HSD1. BVT-2733 is a relatively novel inhibitor of 11β-HSD1 and has been used in previous studies (18) The data indicated that inhibition of 11β-HSD1 by BVT-2733 prevented the development of arthritis and joint destruction in CIOA. In addition, the protective effects of BVT-2733 were shown to be mediated by the inhibition of certain inflammatory signaling pathways.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, several reports have suggested a potential link between a specific expression profile of lipid droplet proteins and brown adipocyte morphology. For example, in animal models, overexpression of perilipin in white fat was associated with reduced lipid droplet size, which may induce BAT-like phenotype (Wang et al 2012). Another study reported that knockout of FSP27, a protein localized in lipid droplets to promote lipid accumulation, induced a phenotype of obesity resistance, elevated oxygen consumption, extremely reduced WAT mass and white adipocyte size, and appearance of multilocular lipid droplets, all reminiscent of a brown fat-like phenotype (Liu et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of 11b-HSD1 could prevent the differentiation of white adipocyte, reduce white adipose accumulation, and improve the function of WAT (London & Castonguay 2009, Staab & Maser 2010. Besides, we recently found that BVT.2733, a selective 11b-HSD1 inhibitor, could even attenuate the inflammation of WAT in diet-induced obese mice (Wang et al 2012). However, the role of 11b-HSD1 in BAT remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%